Handbook of digital forensics of multimedia data and devices - Ho, Anthony T. S., 1958- (Hoboken : Wiley, 2015)
"Focuses on the interface between digital forensics and multimedia forensics, bringing two closely related fields of forensic expertise together to identify and understand the current state-of-the-art in digital forensic investigation"--
7.2 Biometrics Performance Metrics7.3 Face: The Natural Means for Human Recognition; 7.4 Ears as a Means of Forensic Identification; 7.5 Conclusions; References; 8 Multimedia Analytics for Image Collection Forensics; 8.1 Introduction; 8.2 Data and Tasks; 8.3 Multimedia Analysis; 8.4 Visual Analytics Processes; 8.5 ChronoBrowser; 8.6 MediaTable; 8.7 An Example Scenario; 8.8 Future Outlook; References; Part Three: Multimedia Device and Source Forensics; 9 Forensic Camera Model Identification; 9.1 Introduction; 9.2 Forensic Source Identification; 9.3 Digital Camera Model Identification
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Criminal investigation -- Technological innovations; Electronics in criminal investigation; Criminal investigation -- Technological innovations; Electronics in criminal investigation; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; Electronic books